A review of recent usability measures in English Language Teaching (ELT) technologies - Cheng L.K.; Puteh F.; Selamat A.; Mohamed F.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Augmented reality; Computational linguistics; E-learning; Software engineering; Teaching; Usability engineering; Current technology; Emerging technologies; English language teaching; Interface interaction; Mobile Learning; Research capacities; Usability; Usability measures; Engineering education